2013
DOI: 10.1007/s00167-013-2620-y
|View full text |Cite
|
Sign up to set email alerts
|

Intra-operative results and radiological outcome of conventional and patient-specific surgery in total knee arthroplasty: a multicentre, randomised controlled trial

Abstract: I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
147
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(159 citation statements)
references
References 14 publications
9
147
2
1
Order By: Relevance
“…Although there was no statistically significant difference between cohorts, our findings, with 48.98 % of outliers in HKA angle and 42.9 % of malalignments in ZMA in the PSI group are puzzling. Similarly to Boonen et al [31], we have no firm explanation as to why the alignment in our series in the PSI group was not superior to the conventional method, and why literature data are so discrepant. Nevertheless, against such a backdrop, we believe our article is a compelling contribution to the discussion on the utility of PSI systems.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…Although there was no statistically significant difference between cohorts, our findings, with 48.98 % of outliers in HKA angle and 42.9 % of malalignments in ZMA in the PSI group are puzzling. Similarly to Boonen et al [31], we have no firm explanation as to why the alignment in our series in the PSI group was not superior to the conventional method, and why literature data are so discrepant. Nevertheless, against such a backdrop, we believe our article is a compelling contribution to the discussion on the utility of PSI systems.…”
Section: Discussioncontrasting
confidence: 79%
“…In their study, designed to compare MRI-based Signature™ PSI with standard instrumentation, better results were obtained with PSI for all of the above angles. Less optimistic results were observed in a multicentre, randomised control trial performed by Boonen et al [31], who found a statistically significant difference in outliers for the LFC angle, with a higher percentage of outliers in the MRIbased Signature™ PSI group than in the conventional group (65 % vs. 49 %, respectively). Stronach et al [23] reported inadequate fit of MRI-based Signature™ PSI.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…This perioperative guiding technique eliminates the use of intra-and extra medullar rods to make bony resections. Previous published results on PSG suggest this to be a good alternative to conventional instrumentation with comparable results, improved radiological outcome and reduced operation time and blood loss [7,[13][14][15][16][17][18][19][20][21][22][23] . This prospective study on PSG between different manufacturers and conventional technique for the implantation of TKA was designed to address the following research questions: Is there a significant difference in outliers in alignment in the frontal and lateral plane between PSG and conventional TKA, secondly between the four individual different PSG systems and thirdly between cut-and pin PSG?…”
Section: Introductionmentioning
confidence: 84%
“…All patients gave informed consent to participate in this prospective study and were operated by a senior knee orthopaedic surgeon (NK) with extensive experience with PSG [15,16] . Patients were not blinded to the type of alignment method used.…”
Section: Methodsmentioning
confidence: 99%